О родовой принадлежности и внутриродовой структуре палеарктических голопалых гекконов (Reptilia, Gekkonidae, Tenuidactylus gen. n.) - Щербак, Н.Н.; Голубев, М.Л. (Вестник зоологии, 1984)
On Generic Assignement of the Palearctic Cyrtodactylus Lizard Species (Reptilia, Gekkonidae). Szczerbak N. N., Golubev M. L.— Vestn. zool., 1984, No. 2. Polyphylel nature of the genus Cyrtodactylus is shown, Palearctic species are assigned to a new Tenuidactlylus gen. n. (type species: Gymnodactylus caspius Eichw ald, 1831) eristic by the absence of thickened basal digital phalangi, lower scale number (8 to 20 heween eye centres versus 30 to 70 in Cyrtodactylus), well pronouced tail segmentation and other characters. The genus is subdivided ino hree subgenera: nomenotypic (included 4 species), Mediodactylus Szczerbak et Golubev, 1977 (type species: Gymnodactylus kotschyi Steindachner, 1870; included 5 species), and Mesodactylus subg. n. (type species: Gymnodactylus kachhensis Stoliczka, 1872; included 5 species). An amaivels of charactors, vartobilly.